On the subfamilial assignment of Platybunoides (Opiliones: Eupnoi: Phalangiidae), with the description of a new species from China - Zhang, Chao; Zhang, Feng (Zootaxa, 2012)
Platybunoides Šilhavý, 1955, currently included in the subfamily Platybuninae Staręga, 1976, is reassigned to Phalangii-nae Latreille, 1802 for the absence of ventral spur in proximal segment of chelicerae, the absence of ventral thorns on pe-dipalpal femur, and the presence of distomesal bump on pedipalpal patella and tibia. A new species, Platybunoides songisp. nov., from Liupan Mountain, Ningxia, China, is described and can be recognized by having a large ocularium, unarmed pedipalps, hairs being restricted to ventral femur, and the presence of a small bump distally on prolateral femur.